Tuan Guru Haji Abdul Hadi Awang (2021). Pemetaan Baharu Dunia Islam. Kuala Lumpur: Pustaka Permata Ummah. 135 Halaman. [ISBN 978-967-19111-3-6] - Mohd Nasir, Badlihisham; Badlihisham, Nur Shafiqah (Journal of Al-Tamaddun, 2022)
The book written by Datuk Seri Tuan Guru Haji Abdul Hadi Awang is actually a brief study to meet the demands of the World Union of Ulama' based in Qatar. The purpose is to make Muslims and non-bias non -Muslims to be fair in realizing that Islam and its followers have long been oppressed. The book also wants to explain about the concept of Al-Irhab which has been distorted by the West to trigger Islamophobia among the world community. The author of the book also revealed some of the evil plans of the West, especially the new mapping of the Islamic world, which in fact has been done in the past. What exactly is the purpose of the West doing it especially the United States that constantly protecting Israel? This review aims to summarize the great plans of the West to ensure the success of the new mapping of the Islamic world. This review also summarizes the recommendations of the author of this book towards strengthening the Islamic world. The strength of this article also contains aspects of the history of the Islamic world that have taken place in relation to the agenda of the new mapping of the Islamic world and some statements by western scholars that strengthen the existence of this agenda. This review also critically criticizes some of the weaknesses of the book for example the reference provided in the book.